Plan de negocios para crear una empresa de ventas de ropa de mujer en la urbanización ciudad verde del cantón Santo Domingo de la provincia Santo Domingo de los Tsáchilas, año 2015. - Herrera Santillán, Maribel Mercedes (2015)
This research work was performed in order to determine the viability of setting up a business selling women's clothing in the city of Santo Domingo, for which a study of market supply and demand in the sector was implemented in order to establish the tastes and consumer preferences; likewise a technical study that yielded the appropriate requirements of the company was conducted. The return on investment was determined through financial study for the creation of the manufacturing company. In the complex "Green City" city of Santo Domingo, the lack of a business selling women's clothing, is generated by low investment and feasibility study, which affects consumer satisfaction, for the study of market has determined that there is a high demand for purchasing this type made of quality material products. The study was executed in order to undertake a company more than create jobs, offer a quality product and really needed which will cover the demand in the female sector of Santo Domingo. The study was feasible, had the necessary resources to implement market research, technical, economic and financial, besides the contribution of various professionals and traders in the city of Santo Domingo had. The results of the market research, technical and economic - financial support and were essential for the implementation of this thesis Based getting in Net Present Value (VAN) $ 16,984.58 demonstrating profitability and Internal Rate Return (TIR), a value of 18.5%, showing a good profit margin for the creation of business.